Structural isomerism leading to variable proton conductivity in indium(III) isophthalic acid based frameworks - Panda, Tamas; Kundu, Tanay; Banerjee, Rahul (Chemical Communications, 2013)
Proton conductivity has been studied thoroughly in two isomeric In(III)-isophthalate based MOFs. In-IA-2D-1 is capable of showing proton conductivity (3.4 x 10(-3) S cm(-1)) under humidified conditions (98% RH), whereas In-IA-2D-2 can conduct protons (2.6 x 10(-5) S cm(-1)) under humidified as well as anhydrous conditions.